2003
DOI: 10.3141/1843-10
|View full text |Cite
|
Sign up to set email alerts
|

Driver En Route Guidance Compliance and Driver Learning with Advanced Traveler Information Systems: Analysis with Travel Simulation Experiment

Abstract: If real-time driver en route guidance advice does not meet driver preferences (e.g., preference for taking the freeway) or the advice is not correct, drivers are very likely to ignore the information, and the guidance system becomes ineffective in their route choice no matter how advanced the system. There is a need to investigate the factors affecting driver compliance with en route guidance advice. A travel simulation experiment was used to investigate significant factors affecting driver route choice behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…The alternate arterial road route is an imaginary route. The arterial road route can be deemed as an alternate route that a real-world VMS-based ATIS recommends to drivers [5,25]. Thus, our SP settings are reasonable, though the employed network at first sight seems simple.…”
Section: Survey Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The alternate arterial road route is an imaginary route. The arterial road route can be deemed as an alternate route that a real-world VMS-based ATIS recommends to drivers [5,25]. Thus, our SP settings are reasonable, though the employed network at first sight seems simple.…”
Section: Survey Methodsmentioning
confidence: 97%
“…Some other studies used SP data from travel simulator experiments (e.g., [17][18][19][20][21][22][23][24][25]). Others used revealed preference (RP) data to model drivers' response behavior (e.g., [26][27][28][29]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other studies contain findings on compliance rates towards advice. Chen and Jovanis (2003) found a compliance rate of 89% in their simulator study. Ben-Elia, Di Pace et al (2013) found average compliance rates between 62% and 82%, depending on the accuracy level.…”
Section: Perspective On Travel Information Affecting Interacting Behamentioning
confidence: 92%
“…For example, a number of studies [7] indicated that a driver's route and the shortest route differ in significant ways and that most drivers use several criteria in selecting their routes. Furthermore, drivers' spatial and temporal experiences produce variations in route selection [8].…”
Section: Introductionmentioning
confidence: 99%